A 2D/1D Algorithm for Effective Cross-Section Generation in Fast Reactor Neutronic Transport Calculations. (3rd October 2018) - Faure, Bastien; Archier, Pascal; Vidal, Jean-François; Buiron, Laurent
Abstract: Fast resolution of the Boltzmann transport equation over a nuclear reactor core presupposes the definition of homogenized and energy-collapsed cross sections. In modern sodium fast reactors that rely on heterogeneous core designs, anisotropy in the neutron propagation cannot be neglected, so three-dimensional (3D) models should be used to efficiently compute those effective cross sections. In this paper, the 2D/1D approximation is carried out to overcome computationally expensive 3D calculations while preserving consistent angular representations of the neutron flux. An iterative procedure is defined to solve the 2D/1D equations and produce coarse group homogenized cross sections that account for 3D transport effects. Accuracy of the algorithm is tested on a realistic model of the ASTRID core showing very good results against Monte Carlo simulations for all neutronic parameters (eigenvalue, sodium void worth, and fission map distribution).